Psychopathology as a cause or consequence of youth gang involvement - Kerig, Patricia (The Oxford handbook of gangs and society, 2024)
This chapter presents a developmental psychopathology framework as an integrative approach to understanding the intertwined connections over time among mental health (MH) problems and youth gang involvement. First, the chapter identifies growing cross-sectional and prospective evidence that provides support for the role of internalizing and externalizing MH problems as both precipitants and consequences of gang membership. The chapter then turns to discussing transdiagnostic perspectives on psychopathology that may provide innovative ways to understand MH problems among gang-involved youth, including potential transdiagnostic facets underlying multiple psychopathologies and transdiagnostic risk factors implicated in the emergence of MH problems and gang involvement, such as trauma exposure. It then introduces novel ideas for future research regarding purported underlying developmental mechanisms that may explain the links between MH and gang involvement. Finally, the chapter discusses implications for fine-tuning MH interventions that will be more effective and accessible for disadvantaged youth at risk for psychopathology and gang involvement.